2022
DOI: 10.1002/ppul.25943
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center PICU present status survey of pediatric sepsis‐related acute respiratory distress syndrome

Abstract: Background: To describe the incidence, clinical features, outcomes, and mortality risk factors of sepsis associated with acute respiratory distress syndrome (ARDS) in pediatric patients. Methods: Patients were included in the study if they met the 2005 version of the International Pediatric Sepsis Consensus Conference and met the Pediatric Acute Lung Injury Consensus Conference (PALICC) definition within 48 h of sepsis diagnosis. Patients were classified as mild, moderate, and severe by the worst oxygenation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The incidence of sepsis-related PARDS was 19.7%, which was comparable to other studies that reported rates ranging from 8.2% to 22%, [ 5 19 20 ]and PICU mortality rate was 30.7% (8/26) which was higher than a recent retrospective study that revealed the PICU mortality rate of sepsis-related PARDS was 24.6%. [ 21 ]A single-center retrospective study involving 203 sepsis-related PARDS from 828 sepsis patients showed that ARDS severity, PRISM III, and the number of organ dysfunction were associated with increased 90-day mortality in sepsis-related PARDS. [ 21 ]They recruited 20 patients with noninvasively ventilated PARDS, whereas our study recruited only patients with invasively ventilated PARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of sepsis-related PARDS was 19.7%, which was comparable to other studies that reported rates ranging from 8.2% to 22%, [ 5 19 20 ]and PICU mortality rate was 30.7% (8/26) which was higher than a recent retrospective study that revealed the PICU mortality rate of sepsis-related PARDS was 24.6%. [ 21 ]A single-center retrospective study involving 203 sepsis-related PARDS from 828 sepsis patients showed that ARDS severity, PRISM III, and the number of organ dysfunction were associated with increased 90-day mortality in sepsis-related PARDS. [ 21 ]They recruited 20 patients with noninvasively ventilated PARDS, whereas our study recruited only patients with invasively ventilated PARDS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ]A single-center retrospective study involving 203 sepsis-related PARDS from 828 sepsis patients showed that ARDS severity, PRISM III, and the number of organ dysfunction were associated with increased 90-day mortality in sepsis-related PARDS. [ 21 ]They recruited 20 patients with noninvasively ventilated PARDS, whereas our study recruited only patients with invasively ventilated PARDS. Our study found that hemato-oncologic patients, low platelet count, high severity score (PRISM III and PELOD), high serum lactate, and high procalcitonin were the risk factors for sepsis-related PARDS.…”
Section: Discussionmentioning
confidence: 99%